Pengaruh Jumlah Masukan dan Varietas Batang Singkong Terhadap Kinerja Mesin Rabakong Tipe TEP-6 - Asmara, Sandi; Kuncoro, Sapto; Suharyatun, Siti; Aditya, Muhammad Alif (Jurnal Agricultural Biosystem Engineering, 2023)
A lot of cassava stem waste is not used and is only left to rot or burned, so the handling of cassava stems into animal feed ingredients is carried out. The purpose of this research is to determine the performance of the TEP-6 type cassava stem chopper in carrying out the shrinking process with the influence of the variety and the number of cassava stem inputs. This research was conducted with quantitative descriptive method, through testing, measurement, hypothesis through mathematical and statistical calculations, as well as in the presence of graphs and statistical analysis. The results of this research are the best capacity in the Kasesart type of input number of 4 stems with a value of 203,867 kg / hour, and the lowest weight loss is in the Kasesart number of input 3 stems with a value of 11,822%, the lowest fuel consumption is at 1,971 l/jam, there is no fatigue in the use of rabakong machines, and there is a high size of the insertion place that is not yet ergonomic.  And there is a certain size or distance in chopping so that it can effective and efficient. Keywords: Cassava Trunk Waste, Chopper Performance, Number of Inputs, Shrinkage, Variety.